Diagnostic significance of fat globules in blood in fulminant‐type fat embolism syndrome. Issue 10 (16th October 2021) - Asakage, Ayu; Fujisawa, Michiko; Takei, Tetsuhiro; Kumagai, Jiro
Abstract: Fat globule detection in the blood in fat embolism syndrome (FES) diagnosis remains controversial. This case illustrates two life‐threatening, possibly FES‐related, episodes with dramatic increases in blood fat globule level. Future studies should aim at evaluating the significance of the quantitative changes in blood fat levels in diagnosing FES. Abstract : Fat globule detection in the blood in fat embolism syndrome (FES) diagnosis remains controversial. This case illustrates two life‐threatening, possibly FES‐related, episodes with dramatic increases in blood fat globule level. Future studies should aim at evaluating the significance of the quantitative changes in blood fat levels in diagnosing FES.